Qptimization design of video encoder quantizer for general DSPs - GAN Yong1; SU Shi-mei2; ZHOU Bing2; QIAN De-pei 1 (Tongxin xuebao)
A new scheme of quantization which was constructed by an optimal quantization matrix was proposed.It was inefficient for the traditional quantization of MPEG video encoders on the general DSPs.Considering the traits of a DSP,which could realized one-step quantization by substituting shift for division.Meanwhile,this scheme used different quantization strategies according to the differences of the types of video blocks to be coded,and avoids the loss of the quality of images with the unified quantization.Experiments had shown that this scheme could obviously improve the efficiency of quantization,and subjective and objective quality of images coded as well.